2015
DOI: 10.1371/journal.pone.0120927
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Changes of Subcutaneous Fat Mass in HIV-Infected Children on Antiretroviral Therapy: A Retrospective Analysis of Longitudinal Data from Two Pediatric HIV-Cohorts

Abstract: ObjectiveLongitudinal studies objectively evaluating changes in regional fat distribution of HIV-infected children assessed by whole body dual energy X-ray absorptiometry (DEXA) are scarce, whilst this long-term effect of HIV and antiretroviral therapy (cART) is an important issue in infected children in need for lifelong treatment.MethodsWe assessed regional fat distribution over time, measured with sequential DEXA-scans in HIV-infected children on cART in cohorts from South Africa (SA) and the Netherlands (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Associations between abnormal body fat distribution and pediatric HIV disease have been established in various studies (60)(61)(62). HIV infection itself is a factor that causes lipodystrophy syndrome in children who are being treated with antiretroviral medications (63) and could refer to abnormal fat accumulation (lipohypertrophy) or localized loss of fatty tissue (lipoatrophy) (64).…”
Section: Nutritional Status Of Hiv-infected Infants and Childrenmentioning
confidence: 99%
“…Associations between abnormal body fat distribution and pediatric HIV disease have been established in various studies (60)(61)(62). HIV infection itself is a factor that causes lipodystrophy syndrome in children who are being treated with antiretroviral medications (63) and could refer to abnormal fat accumulation (lipohypertrophy) or localized loss of fatty tissue (lipoatrophy) (64).…”
Section: Nutritional Status Of Hiv-infected Infants and Childrenmentioning
confidence: 99%
“…The etiologies of these complications in PLWH are not entirely known but may be associated with a complex interaction between consequences of the virus itself, chronic use of ARVs, and underlying inflammatory processes. Previous studies have demonstrated a link between metabolic abnormalities, lipodystrophy, and most classes of ARVs, including nucleoside reverse transcriptase inhibitors (NRTIs), 4,5 non-NRTIs, 6 and protease inhibitors (PIs). 7,8 More recently, the advent of integrase strand transfer inhibitors, in particular dolutegravir, has also been associated with considerable weight gain and other related metabolic complications.…”
Section: Introductionmentioning
confidence: 99%
“…Based upon data from UNAIDS-Joint United Nations Programme on HIV/AIDS there are approximately 5.2 million children, adolescents, and young adults living with HIV younger than 24 years globally. Prior descriptive studies have demonstrated that exposure to PIs (7)(8)(9), NRTIs (9)(10)(11)(12), and NNRTI (8) alone or in combination contribute to lipodystrophy. Lipodystrophy can be disfiguring and stigmatizing for CHIV.…”
mentioning
confidence: 99%